THE EVOLUTION OF THE ROMANIAN VEGETABLE INDUSTRY AND SOME PROSPECTS FOR THE FUTURE - Cornelia ALBOIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this paper is to analyse the evolution of the fruit and vegetable processing industry in Romania, using several specific indicators that allowed placing the Romanian industry in a European context based on Eurostat data. Based on these developments, another important indicator was calculated with the help of which the degree of food security can be appreciated, namely the degree of self-sufficiency for the main group of vegetables, and forecasts were made regarding its evolution in the medium and long term. The results show that the prognosis remains pessimistic in the sense that Romania will not be able to attain self-sufficiency in the short and medium term, unless the sector is prioritised for important investments in vegetable processing and sector organisation, although some signs of growth opportunities were identified in the analysis.